Male and Female Profanity in English Anecdotes - Knyazyan, Anna (Armenian Folia Anglistika, 2016)
The article covers the problem of profanity and deprecating humor in English anecdotes. Aggressive humor often occurs in the form of sarcasm or teasing and often includes compulsive displays of humor with little regard for others. It deals with the issue of using swearwords in comic discourse. Swearing is a behavior more frequently engaged in by males than by females. Various generalizations about women and men involve some false assumptions as they negate the aspirations, diverse identities and personalities of individual males and females. On the largest scale women are the brunt of more jokes than men.